The Concept Integration Of Science and Theology M. Amin Abdullah's Perspective - Fian, Khafifatul; Gangsar Edi Laksono; Muhammad Masruri (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
There is a debate among several sciences because there is no room for discussion so each science claims it is right. The current era deserves the spirit of integration of science to overcome this, especially between science and religion (theology). The purpose of this paper is to describe and analyze the concept of integration of science and theology from the perspective of M. Amin Abdullah. The method that researchers use is a literature study, data is analyzed based on content (content analyze). After analysis, conclusions are drawn. The results showed that the integration of M. Amin Abdullah's science was called the spider web. He revealed that spider webs have a theoanthropocentric-integralistic pattern. The integration of science between science and religion (theology) has special implications for Islamic education for example, environmental theology which in Islamic education is taught the importance of environmental conservation. Thus, the integration of science with religion (theology) provides awareness to every human being to protect the environment as well as grounding environmental theology and cultivating clean living.